Clinical and Pathophysiological Insights Into Immunological Mediated Glomerular Diseases in Childhood - Mastrangelo, Antonio; Serafinelli, Jessica; Giani, Marisa; Montini, Giovanni (Frontiers in Pediatrics, 2020)
The kidney represents very often the target of immune system dysregulation in the context of primary or systemic disease. In particular, the glomerulus, represents the anatomical entity most frequently involved, generally as expression of the inflammatory cells’ invasion or circulant or in situ immune-complexes deposition. Glomerulonephritis are the most common clinical and pathological manifestation of this involvement. There are no universally accepted classifications for glomerulonephritis. Anyway, recent advances in understanding of pathophysiological mechanisms suggested to take into account immunological features, biomarkers, and genetic assessment. In the same time, more accurate and targeted therapies developed. Data on pediatric glomerulonephritis are few and often derived from adult studies. In this review, we update the current understanding of the etiologic events and genetic factors involved in the pathogenesis of pediatric immunologically mediated primitive forms of GN, together with the clinical spectrum and prognosis. Possible new therapeutic targets are also briefly discussed.